Study of Mechanical and Tribological Properties of Nanomica Dispersed Hydroxyapatite Based Composites for Biomedical Applications - Anumeha Mishra; Nidhi Khobragade; Koushik Sikdar; Subhabrata Chakraborty; Sashi Bhusan Kumar; Debdas Roy (Advances in Materials Science and Engineering)
Present research aims to assess the influence of nanocrystalline mica (NM) dispersion (10, 15, 20, and 25 vol.%) in hydroxyapatite (HA) matrix on its mechanical and tribological properties and bioactivity. Nanosized mica (NM) was prepared by mechanical milling of commercial mica powder. The composite was prepared by mechanically mixing the milled mica with HA and consolidated by microwave sintering at 1200°C for 10 min. Phase characterization by X-ray diffraction (XRD) shows dissociation of HA into β-TCP (tetra calcium phosphate) in sintered compact. Estimated densification is the highest (~98%) with 20% NM addition. HA-20%NM also shows an optimum combination of mechanical (hardness 2.80 GPa and indentation fracture toughness 1.51 MPa m1/2) and tribological properties (wear rate ~1.6 × 10−6 mm3/Nm). Scanning electron microscopy (SEM) of worn out surface elicits that wear mechanism is governed mainly by delamination and abrasive mode. Biocompatibility assessment in simulated body fluid (SBF) indicates that no elemental change occurs (confirmed by energy dispersive spectroscopy (EDS)) even after 60 days of emersion. It reveals that the optimized composition is satisfying fundamental requirements of an implant material.